2022
DOI: 10.1002/srin.202100818
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation on Motion and Removal of Inclusions in Continuous Casting Tundish with Multiorifice Filter

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/srin.202100818.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Inclusion removal is a crucial step in the steelmaking process, and the removal effect directly affects steel quality [1][2][3][4]. At present, the main methods of inclusion removal include gas stirring in ladles [5][6][7][8][9][10], Ruhrstahl-Heraeus treatment [11][12][13][14], slag washing [15][16][17], bubble flotation [18], removal in tundishes [19][20][21][22], and continuous casting mold [23][24][25][26], among others. These methods promote inclusions to float to the slag-steel interface so that the inclusions are more easily removed by refining slag absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Inclusion removal is a crucial step in the steelmaking process, and the removal effect directly affects steel quality [1][2][3][4]. At present, the main methods of inclusion removal include gas stirring in ladles [5][6][7][8][9][10], Ruhrstahl-Heraeus treatment [11][12][13][14], slag washing [15][16][17], bubble flotation [18], removal in tundishes [19][20][21][22], and continuous casting mold [23][24][25][26], among others. These methods promote inclusions to float to the slag-steel interface so that the inclusions are more easily removed by refining slag absorption.…”
Section: Introductionmentioning
confidence: 99%
“…The study revealed that such devices are instrumental in modulating steel flow and extracting inclusions. Liu et al 19,20 demonstrated through simulations that retaining walls, coupled with filtration, can regulate flow and capture inclusions, with retaining walls additionally aiding in the contact and removal of inclusions at the steel-slag interface. Ramirez et al 21 analyzed a five-strand asymmetric tundish using multiphase flow simulations to uncover that dam design optimisation leads to better molten steel flow patterns and inclusion flotation.…”
Section: Introductionmentioning
confidence: 99%
“…This entails optimizing flow control devices [12,13], adjusting process parameters [14,15], implementing gas blowing in the tundish [16,17], and utilizing induction heating technology [18,19]. These endeavors aim to continuously improve the tundish flow field [20,21], temperature distribution [22,23], and enhance inclusion removal efficiency [6,24,25], ultimately elevating the quality of steel products.…”
Section: Introductionmentioning
confidence: 99%